KEKUATAN ALAT BUKTI PRINT OUT SHORT MESSAGE SERVICE DALAM PROSES PEMBUKTIAN BERDASARKAN UNDANG- UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Sulastri '; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The message of short service (SMS) as of documents in electronic trading losses resulting in the very complicated, because inaccessible displayed, guaranteed whole, and could be accounted for a situation that explains.This clearly different from evidence in the conventional shaped writing. The law is the kind of research normative juridical law that are prescriptive, using methodology or study documentary literature.From the research, obtained the result of recognition legislation to short message as a means of legal evidence legitimate .Things are arranged in the provisions of a statute number 11 year 2008 about information and electronic transaction said that information electronic and / or document electronic is a legal evidence legitimate .Short message has qualified as of information and electronic documents as regulated by law so the is considered as a means of legal evidence legitimate. A The message of short service (SMS) as a means of evidence regarded as the expansion of a tool evidence which is valid based on law the event indonesiaWhile relations electronic transaction with life global is to create trade cross-border because conducted electronically through technology information and be instruments effective in global trade.Input from the study are government should put special regulations governing electronic transaction through short message service and admitted The message of short service (SMS) as a means of legal evidence legitimate that stands alone, not the expansion of a tool other evidence.Keywords : Strength of Evidence Print - Out Short Message Service